Multi-Drug Resistant Organisms Infection Impact on Patients Length of Stay in Respiratory Care Ward - Yi-Ping Chen; Xian-Wen Tasi; Ko Chang; Xuan-Di Cao; Jung-Ren Chen; Chien-Sen Liao (MDPI AG, 2021)
This study aimed to investigate the effects of multi-drug-resistant organism (MDRO) infection and other factors on the length of hospital stay (LOS) of patients in the respiratory care ward (RCW) of a regional hospital in Taiwan. In this retrospective study, we collected cases from MDRO-infected patients in the RCW from January 2016 to March 2020. The RCW comprises 13 beds in total. There were 106 infected patients, of which 42 were in the case group (infected with MDROs) and 64 were in the control group (not infected with MDROs). Clinical specimens were inoculated in a selective medium to isolate the pathogenic bacteria by standard procedures. The results showed the main factors affecting the LOS were: patients with MDRO infection, patients discharged from the RCW, and patients who underwent catheterization. The LOS of patients infected with MDROs was significantly longer than that of patients without MDRO infection (β = 0.55, 95% CI = 0.02-1.09), with the case group and the control group being 479.8 ± 546.5 and 307.3 ± 436.2 days, respectively. Infection with carbapenem-resistant Pseudomonas aeruginosa (CRPA) was associated with a longer LOS than other MDRO strains. These findings have important implications for infection control in RCW and in better tracking the health of patients.